The Role of Professional Skills and Re-Training of Medical Staff in Health Protection - Urazalieva I. R.; Rasulova D. S. (Scientific Trends, 2025)
The main task of the Republic of Uzbekistan in the field of healthcare is to provide quality medical services and ensure their accessibility for all segments of the population. This task is effectively achieved by organizing quality education at the pre-university and post-university stages of training medical specialists.